2012
DOI: 10.1177/1479164112451473
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of using one- or two-HbA1c cut-point strategies to detect undiagnosed type 2 diabetes and impaired glucose regulation within a multi-ethnic population

Abstract: Introduction:We compared test performance and cost per case for strategies detecting diabetes on the oral glucose tolerance test (OGTT) using either (a) glycated haemoglobin (HbA1c) ≥ 6.5% (48 mmol/mol) or (b) two HbA1c thresholds where the first cut-point 'rules out' and the second 'rules in' diabetes. HbA1c values in between the thresholds require confirmatory glucose testing for diagnosis. Materials and methods:We conducted an analysis of adults aged 40-75 years from the Leicester Ethnic Atherosclerosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…Although the AUROC in our study was high, the low sensitivity of HbA1c for OGTT-defined diabetes and prediabetes was in line with previous studies in various ethnic groups [8,10,11,21-23]. For instance, a recent cost analysis in a South Asian population aged 40–75 years in the UK reports low sensitivity of HbA1c (at >6.5%) for diabetes [23].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although the AUROC in our study was high, the low sensitivity of HbA1c for OGTT-defined diabetes and prediabetes was in line with previous studies in various ethnic groups [8,10,11,21-23]. For instance, a recent cost analysis in a South Asian population aged 40–75 years in the UK reports low sensitivity of HbA1c (at >6.5%) for diabetes [23].…”
Section: Discussionsupporting
confidence: 89%
“…For instance, a recent cost analysis in a South Asian population aged 40–75 years in the UK reports low sensitivity of HbA1c (at >6.5%) for diabetes [23]. Although many studies have reported a relatively high specificity, a study in India – similarly to our study – found low specificity of HbA1c, particularly for prediabetes [8,10,11,21-23]. The lower optimal HbA1c threshold for prediabetes in our population was in line with the threshold that the Indian study recommended [10].…”
Section: Discussionmentioning
confidence: 99%
“…TA B L E 3 Prevalence of moderately increased albuminuria and UACR values by diabetes status according to HbA1c and FPG/2 h-PGFirst, the cross-sectional approach does not allow proving a causal relationship between the increased FPG/2 h-PG levels among individuals with normal HbA1c levels and the increased prevalence of moderately increased albuminuria, which would require longterm longitudinal follow-up studies. Thus, our results might not be applicable to populations with other ethnicities, since it has been shown that results may vary depending on ethnicity and race 15. The solid curve shows the remaining discriminative performance of the HbA1c levels.…”
mentioning
confidence: 88%
“…6,7 Some guidelines, including those of the German Diabetes Association, recommend a stepwise diagnostic approach using HbA1c as a first screening test with two different cut-off values for the diagnostic decision, of which the lower cutoff is used to rule out diabetes and the higher cut-off is used to diagnose diabetes without measuring FPG and/or two-hour postload glucose levels (2 h-PG). [11][12][13][14][15][16][17][18][19][20][21][22][23][24] Importantly, stepwise diabetes screening strategies using only HbA1c as first-instance diagnostic parameter may cause failure to detect individuals with abnormal glucose regulation and possible signs of microvascular complications despite HbA1c levels below the "rule-out" cut-off. [8][9][10] Despite the advantages of HbA1c-based diabetes screening, there is an ongoing debate about the usefulness of this marker to detect individuals with diabetes and prediabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation